2013
DOI: 10.1051/0004-6361/201322422
|View full text |Cite
|
Sign up to set email alerts
|

Why the globular cluster NGC 6752 contains no sodium-rich second-generation AGB stars

Abstract: Context. Globular clusters host multiple stellar populations showing different sodium enrichments. These various populations can be observed along the main sequence, red giant and horizontal branch phases. Recently it was shown, however, that at least in the globular cluster NGC 6752, no sodium-rich stars are observed along the early asymptotic giant branch (AGB), posing an apparent problem for stellar evolution. Aims. We present an explanation for this lack of sodium-rich stars in this region of the colour-ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 32 publications
8
41
1
2
Order By: Relevance
“…The absence of very He-rich stars that we predict along the AGB agrees with the observations of Campbell et al (2013), who reported a lack of very Na-rich AGB stars in the old GC NGC 6752 (see also Charbonnel et al 2013;and Wang et al 2016). However, in contrast to Campbell and collaborators, who concluded that in this GC all 2P stars fail to climb the AGB, we obtain that ∼74% of the AGB stars at 13 Gyr belong to the 2P with the current model assumptions.…”
Section: Asymptotic Giant Branchsupporting
confidence: 89%
See 3 more Smart Citations
“…The absence of very He-rich stars that we predict along the AGB agrees with the observations of Campbell et al (2013), who reported a lack of very Na-rich AGB stars in the old GC NGC 6752 (see also Charbonnel et al 2013;and Wang et al 2016). However, in contrast to Campbell and collaborators, who concluded that in this GC all 2P stars fail to climb the AGB, we obtain that ∼74% of the AGB stars at 13 Gyr belong to the 2P with the current model assumptions.…”
Section: Asymptotic Giant Branchsupporting
confidence: 89%
“…Despite the above-mentioned limitation and as already discussed in Papers I, II, and Charbonnel et al (2013), we can conclude that only stars with Y ini lower than 0.41 populate the HB at 13 Gyr in our synthetic GC (see Fig. 6).…”
Section: Highest Helium Content On the Horizontal Branchcontrasting
confidence: 40%
See 2 more Smart Citations
“…As mentioned previously, a commonly adopted solution is that Na-rich stars have a higher He abundance, and that the lower masses of He-rich/Na-rich horizontal branch stars prevent them from evolving through the AGB phase. At least for the extreme case of NGC 6752, Charbonnel et al (2013) note that stars with masses less than about 0.735 M e and Y  0.31 do not ascend the AGB. However, the required He-enhancements are significantly larger than those estimated from photometry (ΔY ∼ 0.03-0.04; Milone et al 2013), but Charbonnel et al (2013) further suggest the maximum photometric He spread could be underestimated.…”
Section: Interpreting the Agb And Rgb [Na Fe] Distributionsmentioning
confidence: 98%